Applying the Theory of Constructed Emotion to Police Decision Making - Fridman, Joseph; Barrett, Lisa Feldman; Wormwood, Jolie B.; Quigley, Karen S. (Frontiers in Psychology, 2019)
Law enforcement personnel commonly make decisions in stressful circumstances, where the costs associated with errors are high and sometimes fatal. In this paper we apply a powerful theoretical approach, the theory of constructed emotion (TCE), to understanding decision-making under evocative circumstances. This theory posits that the primary purpose of a brain is to predictively regulate physiological resources to coordinate the body’s motor activity and learning in the short-term, and to meet the body’s needs for growth, survival, and reproduction in the long-term. This process of managing the brain and body’s energy needs, called allostasis, is based on the premise that a brain anticipates bodily needs and attempts to meet those needs before they arise (e.g., raising blood pressure before standing), because this is more efficient than responding to energetic needs after the fact. In this view, all mental events—cognition, emotion, perception, and action— are shaped by allostasis, and thus all decision making is embodied, predictive, and concerned with balancing energy needs. We also posit a key role for the autonomic nervous system (ANS) in regulating short-term energy expenditures, such that the ANS influences experience and behavior under stressful circumstances, including police decision making. In this paper, we first explain the core features of the TCE, and then offer insights for understanding police decision making in complex, real-world situations. In so doing, we describe how the TCE can be used to guide future studies of realistic decision making in occupations in which people commonly make decisions in evocative situations or under time-pressure, such as in law enforcement.